2016
DOI: 10.1088/1741-2560/13/4/046008
|View full text |Cite
|
Sign up to set email alerts
|

Changes of intranetwork and internetwork functional connectivity in Alzheimer’s disease and mild cognitive impairment

Abstract: Our results confirmed previous findings that AD pathology was related to dysconnectivity both within and between resting-state networks but revealed more spatial details. Moreover, the SAL network, reportedly flexibly coupling either with the DAN or DMN networks during different brain states, demonstrated interesting alterations specifically in the early stage of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 64 publications
4
47
0
Order By: Relevance
“…A previous study demonstrated that interactions among the SN, ECN, and DMN are involved in working memory load [82]. Abnormal FCs among the ECN, DMN, and SN have been shown to contribute to cognitive decline in Alzheimer's disease patients [83]. Thus, our results suggest that DR patients might also exhibit cognitive decline.…”
Section: (C)supporting
confidence: 55%
“…A previous study demonstrated that interactions among the SN, ECN, and DMN are involved in working memory load [82]. Abnormal FCs among the ECN, DMN, and SN have been shown to contribute to cognitive decline in Alzheimer's disease patients [83]. Thus, our results suggest that DR patients might also exhibit cognitive decline.…”
Section: (C)supporting
confidence: 55%
“…The FC between a seed and each voxel within another network mask, e.g., FC between PCC (the seed for the DMN) and each voxel within the FPCN or the DAN, was defined as the internetwork FC. This method contributes to identifying the functional differences of core regions in each network [27]. The between-group FC differences were analyzed by using a voxel-wise one-way analysis of covariance, controlling for age, sex, and years of education (using DPABI v2.3).…”
Section: Methodsmentioning
confidence: 99%
“…Aberrant inter-network functional connectivity between the DMN and the SAL were reported in older adults with or without cognitive impairment (27, [63][64][65]. Moreover, functional connectivity between these two networks has been linked to executive function performance (66).…”
Section: Discussionmentioning
confidence: 99%